Use of a ring retractor to facilitate specimen removal in laparoscopic surgery - Deok Ho Hong; Miseon Kim; Kidong Kim; Dong Hoon Suh; Jae Hong No; Yong Beom Kim (Korean Society of Obstetrics and Gynecology, 2020)
Objective To introduce a new surgical technique for specimen removal during laparoscopic surgery. Methods The surgical technique was described, pictured, and recorded. The surgery was performed in a tertiary hospital. Results During laparoscopic surgery, the specimen is resected from the surrounding tissues and contained in a specimen bag to prevent spillage. The edges of the bag are then pulled through the trocar site, and the specimen-protected by the bag-is removed. To facilitate the removal process and to prevent spillage, assistants will normally hold the edges of the bag during the process. To mitigate the need for assistants to hold the edges of the bag, we wrapped the pulled edges of the bag around a ring retractor, which is a plastic ring, to straighten the bag. This technique enabled the operator to remove the specimen without needing an assistant. Conclusion The technique we describe here, using a ring retractor for specimen removal, is useful when assistants are unavailable to help during laparoscopic surgery.